Analysis of Capital Structure, Profitability, and Liquidity on Indonesia Stock Exchange’s Company Dividend Distributed 2016-2020 - Raihandhika Akbar; Ediwarman (School of Business, IPB University (SB-IPB), 2022)
Quantitative study approach was used to find out whether there is an influence between capital structure, profitability, and liquidity on the dividend distributed of the IDX80 company for the 2016-2020 period. The population in this study was drawn from companies listed on the Indonesia Stock Exchange using a purposive sampling approach, therefore 31 IDX80 companies were gathered during a five-year period, yielding 155 sample data in this study. Regression analysis technique was used in this study panel data with EViews Version 12 program and a significance level of 5% or 0.05. The results of this study indicate that: 1) there is no effect of the capital structure variable on dividend distributed, 2) there is an effect of the profitability variable on dividend distributed, 3) there is an effect of the liquidity variable on dividend distributed. The investors who will invest in the BEI will pay attention to the Profitability (ROA) and Liquidity (CR) of the company because it has a positive effect. Keywords: capital structure, profitability, liquidity, dividend distributed, IDX80